1986
DOI: 10.1002/ana.410200305
|View full text |Cite
|
Sign up to set email alerts
|

PET scan investigations of Huntington's disease: Cerebral metabolic correlates of neurological features and functional decline

Abstract: Fifteen drug-free patients with early to midstage Huntington's disease were evaluated with quantitative neurological examinations, scales for functional capacity, computed tomographic (CT) scans, and positron emission tomographic (PET) scans of 18F-2-fluoro-2-deoxyglucose (18F-FDG) uptake. All patients had abnormal indices of caudate metabolism on PET scanning, whereas in patients with early disease indices of putamen metabolism and CT measures of caudate atrophy were normal. Indices of caudate metabolism corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(106 citation statements)
references
References 23 publications
8
94
0
4
Order By: Relevance
“…This study showed significant hypometabolism in the caudate nucleus of gene mutation carriers as compared with mutation-negative subjects [9]. These first discoveries were followed by several years of relevant scientific research activity on HD which confirmed the preliminary reports and showed a significant relationship between striatal and cortical hypometabolism and motor impairment progression and cognitive changes [10][11][12]. Hayden et al found significant caudate nucleus hypometabolism in a cohort of mutation-positive subjects with no signs of cortical or striatal atrophy [13], and later Ciarmiello et al found that striatal hypometabolism is significantly correlated with the estimated age at onset [14].…”
supporting
confidence: 83%
“…This study showed significant hypometabolism in the caudate nucleus of gene mutation carriers as compared with mutation-negative subjects [9]. These first discoveries were followed by several years of relevant scientific research activity on HD which confirmed the preliminary reports and showed a significant relationship between striatal and cortical hypometabolism and motor impairment progression and cognitive changes [10][11][12]. Hayden et al found significant caudate nucleus hypometabolism in a cohort of mutation-positive subjects with no signs of cortical or striatal atrophy [13], and later Ciarmiello et al found that striatal hypometabolism is significantly correlated with the estimated age at onset [14].…”
supporting
confidence: 83%
“…Previous studies of cerebral metabolism in vivo in HD have not addressed this issue. They have almost exclusively concentrated on measurements of glycolytic, not oxidative, metabolism, reporting early reductions in both the caudate and putamen (11)(12)(13)(14). Only a single case study has reported measurements of striatal oxidative metabolism (15).…”
mentioning
confidence: 99%
“…40 -42 Levels of resting putamen metabolism correlate with locomotor function and caudate metabolism with performance on tests sensitive to frontal lobe function. 43,44 In early HD, cortical metabolism is preserved but as the disease progresses and dementia becomes prominent it also declines, with the frontal cortex being targeted. 45 Reduced caudate glucose metabolism has been reported in between 38% and 75% of asymptomatic adult HD gene carriers in various series.…”
Section: Resting Metabolic and Activation Studiesmentioning
confidence: 99%